2015
DOI: 10.1093/pasj/psv075
|View full text |Cite
|
Sign up to set email alerts
|

Soft X-ray observation of the prompt emission of GRB 100418A

Abstract: We have observed the prompt emission of GRB 100418A from its beginning by the MAXI/SSC (0.7-7 keV) on board the International Space Station followed by the Swift/XRT (0.3-10 keV) observation. The light curve can be fitted by a combination of a power law component and an exponential component (decay constant is 31.6 ± 1.6 sec).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, Kagawa et al (2015) reported that the exponential temporal decay model was able to fit some extended emissions with an e-folding time of 50 -100 seconds. Similar studies on the exponential decay has been performed for early X-ray emissions of long GRBs (LGRBs) (e.g., Willingale et al 2007;Sakamoto et al 2007;Imatani et al 2016). Therefore, in this paper, we report a systematic study on phenomenological modeling for the extended emission light curves of SGRBs by adopting the exponential and power-law decay models, and a comparison of both models for discussing which model is suitable for describing the observed light curves of the extended mission.…”
Section: Introductionmentioning
confidence: 61%
“…On the other hand, Kagawa et al (2015) reported that the exponential temporal decay model was able to fit some extended emissions with an e-folding time of 50 -100 seconds. Similar studies on the exponential decay has been performed for early X-ray emissions of long GRBs (LGRBs) (e.g., Willingale et al 2007;Sakamoto et al 2007;Imatani et al 2016). Therefore, in this paper, we report a systematic study on phenomenological modeling for the extended emission light curves of SGRBs by adopting the exponential and power-law decay models, and a comparison of both models for discussing which model is suitable for describing the observed light curves of the extended mission.…”
Section: Introductionmentioning
confidence: 61%
“…This identifies GRB 100418A as a long GRB according to the classical division (Kouveliotou et al 1993), but also as a prototypical intermediate burst, according to the definition of Horváth et al (2010), with a probability of 0.998 of belonging to this class. The prompt emission was also detected in the soft X-ray band by MAXI SSC (Imatani et al 2016).…”
Section: Observationsmentioning
confidence: 90%